Dispute Resolution Model for Procurement of Government Goods and Services from State Administrative Law Perspective - Hafidz, Jawade; Pamungkas, Achmad J (Faculty of Law, Universitas Pekalongan, 2024)
Agreements for the procurement of goods/services with the principles of State Administration law are basically the same as agreements and generally give rise to rights and obligations of the parties which are called achievements. If these achievements are not fulfilled or there is a default by one of the parties, this will ultimately lead to a dispute between the parties. In this regard, the main problem studied is the model for resolving disputes over government procurement of goods and services agreements from a State Administrative Law perspective. The research method used is Normative Juridical which is based on secondary data. The results of the research show that the resolution of disputes over agreements for the procurement of Government Goods and Services from the legal perspective of the State Administration is carried out through non-litigation channels (Consultation, Mediation and/or Arbitration), while the Litigation route can be submitted to the Court within its absolute competence, namely the State Administrative Court, District Court by means of file a simple lawsuit or ordinary event lawsuit.